PS 11-39 TO STUDY USEFULNESS OF AMBULATORY BLOOD PRESSURE MONITORING IN PATIENTS OF METABOLIC SYNDROME AND ITS CORRELATION WITH VARIABLES OF METABOLIC SYNDROME. (September 2016) - Shakya, Shobhit; Kumar, Dhiraj; Sawlani, Kamal; Atam, Virendra; Usman, Kauser; Chaudhary, Shyam; Himanshu, Dandu
Abstract : Objective: To study (1)usefulness of Ambulatory Blood Pressure Monitoring in patients of Metabolic Syndrome and (2) its correlation with variables of Metabolic Syndrome. Design and Method: A prospective observational study was conducted in the Department of Medicine, KGMU, Lucknow. Persons aged 20–65 years having metabolic syndrome as defined by IDF criteria 2006, were included in the study. Exclusion criteria include age > 65 years, secondary hypertension, endocrine disorders including acromegaly, Cushing's disease, and thyroid disorders, pregnancy, clinical neurological disease with autonomic dysfunction, and obstructive sleep apnoea. Subjects underwent 24-h ABPM with CONTEC 06 fully automated ABPM machine. With predefined instructions. Statistical analysis was done with SPSS 16.0 software. Results: Out of 53 patients, 38 were detected hypertension by ABPM against 29 by office blood pressure measurement. On the basis of average ABMP, day ABPM and night ABMP, the proportion of hypertensives was 42.3%, 30.8% and 73.1% respectively. Only 16 of 38 had raised mean day blood pressure. Non-dipping pattern (n = 28; 52.8%) reverse dipping pattern (n = 18; 34%) dipping pattern (n = 7; 13.2%). With increasing number of metabolic syndrome components an increase in proportion of patients with non-dipping and reverse dipping pattern was observed (p < 0.001). Conclusions: ABPM is superior to office blood pressure in detecting hypertension in patients with MS (Hodgkinson et al). ABPM is useful to detect nocturnal hypertension. Absence of dipping is quite common in Metabolic syndrome patients (Ayala et al, Vyssoulis et al, Tartan et al). 5 out of 16 patients who were on antihypertensive medication were found to have masked uncontrolled hypertension on ABPM. Thus ABPM can be used for monitoring of treatment efficacy of patients on antihypertensive treatment. ABPM should be done in all patients with Metabolic Syndrome. Large scale studies are required in Indian patients to detect exact prevalence of hypertension, dipping pattern and other variables detected by ABPM.